Analysis of the Opportunities for Financial Support of Municipal Projects in the Social and Cultural Area under the Operational Programme „Regional Development” in the Period 2007–2013 - Trifonova, Silviya (Research Papers, 2009)
The main objective of the study is to analyze the current financing opportunities for support of municipal projects in the social and cultural area which are provided by the Operational Programme “Regional Development” during the period 2007-2013. Bulgaria’s membership into the European Union imposes the need of a clear understanding and efficient management of the European mechanisms for financial support of human resources development, social infrastructure and sustainable and balanced regional development in order to be achieved a higher competitiveness of the economy, lower regional disparities and a higher standard of living. Actuality of the study is undisputable since the municipalities are the main actors in the process of planning and absorption of European funds. However, they still face problems of insufficient financial and administrative capacity for elaborating projects and absorbing funds, and only partially use the opportunities for partnerships. With this aim, in the current study is made a thorough analysis of the present situation and the problems and challenges ahead of the local administrations in Bulgaria particularly with regard to their activities in the social and cultural area. On this basis a profound research of the National Strategic Reference Framework of the Republic of Bulgaria is made with a particular attention on the Operational Programme “Regional Development”. The main focus is put on the schemes and opportunities for provision of financial support to municipal projects in the social and cultural area.